PENGARUH LITERASI KEUANGAN TERHADAP PEMILIHAN LAYANAN KEUANGAN SYARIAH - Panghayo, Novia Ari; Musdhalifah, Musdhalifah (Universitas Negeri Surabaya, 2018)
This study aims to examine the influences of financial literacy which proxied by variables of education, income and knowledge on the selection of Sharia Financial Services in Jombang District. The data was primary data which obtained by method of spreading the questionnaire in the sub-districts with the largest moslem population in Jombang. Research period was in April to May 2017. Sampling method used is incidental sampling and analysis method used is Partial Least Square (PLS). The results of this study indicate that the level of education and income do not affect the selection of Sharia Financial Services in Jombang, while the level of knowledge affect the selection of Sharia Financial Services in Jombang. The implication of this research is that Sharia Financial Services in Jombang Regency is more influenced by knowledge variables, so the government is expected to increase the society insight through socialization about syariah financial literacy, and sharia products.